A Canadian Alternative to the "Clash of Civilizations" - Keren, Michael (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
This article shows how Yann Martel's novel Life of Pi, following a well-established Canadian tradition of breaching cultural divides, provides an alternative to the "clash of civilizations" theory prevalent in today's international arena. It argues that the novel challenges three foundations of the theory—the consideration of religious revival in contradiction to scientific rationality, the tying of civilization to the negation of other civilizations, and the assumption that conflict between civilizations is immanent—and proposes an alternative of coexistence between civilizations, consistent with Canadian foreign policy norms.